Barriers to the provision of high‐quality palliative care for people with dementia in England: a qualitative study of professionals' experiences. (27th December 2013) - Davies, Nathan; Maio, Laura; Vedavanam, Krish; Manthorpe, Jill; Vernooij‐Dassen, Myrra; Iliffe, Steve; the IMPACT Research Team
Abstract Approaches to palliative care that were originally developed for people with cancer are now being adopted for people with dementia, as a response to many reports of poor‐quality care for people with dementia at the end of life. This study explored perceived barriers to the delivery of high‐quality palliative care for people with dementia using semi‐structured interviews. Recordings were transcribed verbatim and analysed using thematic analysis with an inductive approach and a coding strategy. To improve the trustworthiness of the analysis, independent reading and coding of the transcripts were undertaken, followed by discussions among the four researchers to reach agreement and consensus of the themes. Two group interviews (n = 7 and n = 6), 16 individual interviews and five interviews of pairs of professionals were conducted in 2011/2012 with participants from backgrounds in palliative care, dementia services, palliative care research and policy making. Four themes were identified as barriers to providing high‐quality palliative care for people with dementia: (i) ambivalence towards the systematisation of palliative care; (ii) disconnection between services; (iii) different assumptions about training needs; and (iv) negotiation of risk. Understanding these barriers to providing high‐quality palliative care for people with dementia could help in the development of a dementia‐specific palliative care pathway.